Spatial Economic-Hydroecological Modelling and Evaluation of Land Use Impacts in the Vecht Wetlands Area - J.C.J.M. van den Bergh; A. Barendregt; A. Gilbert; M. van Herwijnen; P. van Horssen; P. Kandelaars (Tinbergen Institute, 2000)
Wetlands provide many important goods and services to human societies, and generate nonuse values as well. Wetlands are also very sensitive ecosystems that are subject to much stress from human activities. Reducing the stress on wetlands requires a spatial matching between physical planning, hydrological and ecological processes, and economic activities. Spatially integrated modelling and evaluation can support this. The present study has developed a triple layer model that integrates information and concepts from social and natural sciences to address the analysis and evaluation of land-use scenarios for a wetlands area in the Netherlands, the Vecht area. This is the floodplain of river Vecht, located in the centre of the Netherlands. The study has resulted in a set of linked spatial hydrological, ecological and economic models, formulated at the level of grids and polders. The main activities incorporated in the system of models are housing, infrastructure, agriculture, recreation and nature conservation. The formulation of alternative development scenarios is dominated by land use and land cover options that are consistent with the stimulation of agriculture, nature or recreation. Two aggregate performance indicators have been constructed from model output, namely net present value of changes and environmental quality. The spatial characteristics of these indicators are retained in a spatial evaluation that ranks scenarios.
Keywords: 330; agriculture; aggregation; nature conservation; performance indicators; recreation; spatial evaluation; vegetation response model; Feuchtgebiet; Bodennutzung; Bewertung; Theorie; Niederlande